2015
DOI: 10.5530/jyp.2015.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of Commercially Available Toothpastes – An In vitro Study

Abstract: Background: The use of antimicrobial chemotherapeutic agent has been proposed as a means of reducing the levels of oral bacteria. Many chemotherapeutic agents claim to have antimicrobial properties. Hence this in vitro study had been undertaken. Methods: This in vitro study comprised of seven toothpastes which have been tested for their antimicrobial activity against three oral pathogens namely, Streptococcus mutans, Escherichia coli and Candida albicans by well agar diffusion assay at the dilution of 1:1, 1:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Sufficient data was not available on the growth of microorganisms after expiration date from other studies as they mostly reported on those which are still consumable state. This increases the importance of the current study, as it allows the better understanding of the patterns of spoilage microorganisms after expiration date, particularly due to the difficulty involved in monitoring the effect of spoiled foods on the consumers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient data was not available on the growth of microorganisms after expiration date from other studies as they mostly reported on those which are still consumable state. This increases the importance of the current study, as it allows the better understanding of the patterns of spoilage microorganisms after expiration date, particularly due to the difficulty involved in monitoring the effect of spoiled foods on the consumers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…Juices can also serve as a vehicle of food borne illness, allowing the growth of spoilage causing microorganisms in its nutrient rich medium (6)(7)(8). In most cases pasteurization is able to eliminate most pathogens but some manage to remain in dormant forms (2,9). The major source of contamination is the water used in the products, others include pH, hygienic practices and temperature (10)(11)(12).…”
Section: Changes Of Microbial Load In Packet Orange Juice After Expirmentioning
confidence: 99%
“…All the fluoride-free dentifrices tested in this study except NF2 showed significant antimicrobial activity against S. mutans . This could be attributed to various ingredients present in these formulations such as sodium lauryl sulfate, 10 xylitol, 11 sorbitol. 12 No clear explanation could be given for the absence of antimicrobial activity of NF2 except that it is fluoride-free, sodium lauryl sulfate-free, and could also be due to the inhibition of active compounds by other ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the American Dental Association (ADA), toothpastes are pastes, gels or powders that help remove plaque, a film of bacteria that forms on teeth and gums. All most all toothpaste contain Silica, Sorbitol, Glycerin, polyethylene, Glycerol, Sodium Carbonate, Laurylsalphate, Carbonate, xanthan, Dioxide inaquesaus base, Calcium, Carbonate, terasodium (9). Among these ingredients some act as antimicrobial agents, they kill microorganisms by disrupting their cell walls and inhibiting their enzymatic activity.…”
Section: Microbiological Analysis Of Commonly Used Toothpaste Samplesmentioning
confidence: 99%